Kesiapan Sekolah dan Peran Guru dalam Implementasi Kurikulum Merdeka: Studi Kasus di MIN 14 Blitar - Ivantri, Rohmah (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This study examines the implementation of the Kurikulum Merdeka at MIN 14 Blitar, identifying various aspects related to lesson planning, implementation strategies, and the role of assessment within the Kurikulum Merdeka approach. In the context of educational changes demanded by the Industrial Era 4.0, the role of teachers in adapting to the new curriculum is a primary focus. Additionally, the readiness of schools in terms of human resources, facilities, and infrastructure is crucial for the successful implementation of this curriculum. The study employs a descriptive qualitative approach to illustrate lesson planning that emphasizes the analysis of learning outcomes, the use of diagnostic assessments, teaching modules, and teachers' understanding of students' learning styles. The findings highlight that the implementation of the Kurikulum Merdeka is supported by the Merdeka Belajar platform, adequate facilities, and various differentiated learning methods. Assessment plays a critical role through initial, formative, and summative assessments, with a transparent grading process facilitated by the Rapor Digital Madrasah (RDM), which involves parents in evaluating students' education.